Integration of Renewable Energy Systems - Walker, Andy, 1953-; Scheib, Jennifer; Turchi, Craig S.; Robicaud, Rob; Tomberlin, Gregg; Burman, Kari; Hillesheim, Michael; Kroposki, Ben; Qu, Ming (The American Society of Mechanical Engineers, 2016)
Energy efficiency measures are generally less expensive than a renewable energy (RE) system to provide the same amount of energy saved. The Energy Information Administration reports that, on average, a dollar spent on efficiency saves.
Keywords: Buildings -- Energy conservation.; Renewable energy sources.; Buildings -- Power supply.; elektronické knihy; electronic books